2007
DOI: 10.1002/jcp.21283
|View full text |Cite
|
Sign up to set email alerts
|

High extracellular inorganic phosphate concentration inhibits RANK–RANKL signaling in osteoclast‐like cells

Abstract: In this work, we investigated the effect of inorganic phosphate (Pi) on the differentiation of monocyte/macrophage precursors into an "osteoclastic" phenotype, and we delineated the molecular mechanisms which could be involved in this phenomenon. This was achieved by stimulating human peripheral blood monocytic cells and RAW 264.7 monocyte-macrophage precursor cells to differentiate into osteoclast-like cells in the presence of receptor activator of NF-kappaB ligand (RANKL) and macrophage colony-stimulating fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 35 publications
1
65
1
Order By: Relevance
“…For example, oxidized phospholipids did not induce RANKL expression in vascular smooth muscle cells. Non-atherogenic factors also inhibit osteoclasts in the vasculature; Mozar et al (42) found that inorganic phosphate inhibits osteoclastic activity by inhibiting JNK and Akt activation. Combined with low expression of osteoclast activators, and secretion of osteoclast inhibitory factors, vascular cells may limit osteoclast formation, thereby promoting a milieu favoring progression of ossification.…”
Section: Table 2 Effect Of Pki On Tnf-␣ Induction Of Ranklmentioning
confidence: 99%
“…For example, oxidized phospholipids did not induce RANKL expression in vascular smooth muscle cells. Non-atherogenic factors also inhibit osteoclasts in the vasculature; Mozar et al (42) found that inorganic phosphate inhibits osteoclastic activity by inhibiting JNK and Akt activation. Combined with low expression of osteoclast activators, and secretion of osteoclast inhibitory factors, vascular cells may limit osteoclast formation, thereby promoting a milieu favoring progression of ossification.…”
Section: Table 2 Effect Of Pki On Tnf-␣ Induction Of Ranklmentioning
confidence: 99%
“…Monocytes were differentiated into osteoclasts by growth on cortical bone slices obtained from bovine femora, 23 in the absence or in the presence of RANKL/MCSF, with or without IL-4. Mature osteoclasts were stained for TRAP expression using a commercially available kit (leukocyte acid phosphatase staining kit; Sigma).…”
Section: Tartrate-resistant Acid Phosphatase Osteoclast Staining and mentioning
confidence: 99%
“…Interestingly, the Pi-dependent activation of the ERK1/2 pathway up-regulated the gene expression of the mineralization inhibitors matrix gla protein (Mgp) and osteopontin (Opn), most likely setting off a feed-back mechanism to control Pi-induced mineralization (7,16,18,19). The elevated extracellular Pi level was also shown to be important in osteoblast proliferation and differentiation (16,(20)(21)(22)(23)(24), cementoblast formation (25), odontoblast differentiation (26,27) and osteoclast differentiation (28)(29)(30).…”
mentioning
confidence: 99%